ChemInform Abstract: An Efficient Aldol‐Type Direct Reaction of Isatins with TMSCH2CN. Issue 6 (21st January 2016) - Bhaskara Rao, V. U.; Kumar, Krishna; Singh, Ravi P.
Abstract: CsF catalyzed direct cyanomethylation of various isatins (I) and (IV) using TMSCH2 CN (II) as nucleophile is developed.